IMPLEMENTATION OF OCCUPATIONAL SAFETY AND HEALTH ON EMPLOYEES PRODUCTIVITY OF PT. LEIGHTON CONSTRUCTION INDONESIA SITE SOROAKO - Suriyanti, Suriyanti; Wahyudi, Wahyudi (Jurnal Ekonomi Balance, 2020)
This research aims to determine whether there is influence in the application of occupational safety and health on the productivity of employees at PT. Leighton contruction Indonesia  site soroako. occupational health and safety is one maintenance form of human resources, in this case maintenance employees means retain employees to remain loyal to the company, improve employee motivation and discipline, improve safety and peace of mind of employees in perform the work, and improve employee performance. The data used in this experience were obtained from questionnaires (primary) and some observations and interviews with employees of PT. Leigthon contruction Indonesia site soroako. The analysis method used is linear regression analysis using hypothesis test, the F test and t test. The results of this study are the results of the regression equation and test data on occupational health and safety on the productivity of the work of the PT.Leigthon contruction, the regression coefficient results and date tests for occupation health and safety variable on the productivity performance of PT. Leigthton  this can be proven by the regression coefficient and data test